Design analysis of the smelting technology and choice of oxygen blow conditions of cord steels with view to reduce nitrogen content - V. V. Filippov; V. I. Timoshpolsky; S. A. Fomenko; A. D. Shevchenko; V. V. Enders (Литьë и металлургия, 2001)
А design analysis of the process of steel smelting in a modem steel smelting furnace is worked out, which includes calculation of furnace feed heating and smelting dynamics, material and thermal balance of the dissolution period. The calculation of choice of metal oxygen blow conditions with the view to reduce nitrogen content with application of this model